Pengaruh Risiko Keuangan dan Intellectual Capital terhadap Nilai Perusahaan Sektor Perbankan - Affandi, Olivia; Wijaya, Trisnadi (Universitas Multi Data Palembang, 2024)
This study aims to determine the effect of financial risk and intellectual capital on firm value. The type of research used is a quantitative approach. The population used in this study are banking companies listed on the Indonesia Stock Exchange for the period 2020-2022. The sampling technique used purposive sampling technique, so that 135 observations were obtained from 45 companies over a 3-year period. Hypothesis testing using multiple linear regression analysis with the help of SPSS software version 26. The results of this study indicate financial risk and intellectual capital have an influence on firm value.